Media Relations di Era Konglomerasi Media - Sumantri Raharjo (Program Studi Ilmu Komunikasi, 2012)
Every organization needs mass media to publish positive news for their image. It will be a serious problem when media is in a ring with the others commercial corporate ownership. Public Relations practitioners have to map all media around them to prevent a blunder strategic to reach organization objective on media relations. It is very risky when organization miss elects the groups of media to reach their goal. A good analysis of media groups mapping can avoid a blunder strategy.